Impact of Interest Rate, Inflation Rate, Exchange Rate and Gold Prices on Karachi Meezan Index 30 - Haider, Syed Wajahat (European Journal of Islamic Finance, 2018)
Stock market performance have a significant impact on economic development of a country. Stock markets are supposed to be affected by different financial and macro-economic variables such as gold and oil prices, inflation rate, interest rate, exchange rate and unemployment rate etc. This study is an attempt to find the impact of financial and macro-economic variables on the Karachi Meezan Index 30, the first Islamic Stock index in Pakistan. Monthly data from July 2011 till June 2016 of the variables KMI Index 30, Interest rate, Inflation rate Exchange rate and Gold price is used in this study to find the impact of Interest rate, Inflation rate, Exchange rate and Gold prices on KMI 30 by using Multiple regression model. The empirical result shows that there is a negative relationship of KMI 30 index with interest rate and gold prices whereas a positive relationship exist between exchange rate and KMI 30 Index. Inflation rate did not show a significant relationship with KMI 30 Index in our regression model.